University proceedings. Volga region. Social sciences - L.V. Rozhkova; V.A. Gladilina (Известия высших учебных заведений. Поволжский регион: Общественные науки)
Background. Professional success is important component of life success. Its components are professional self-realization, career, high status, good pay, and respect from colleagues. Student youth have not yet entered the labor market, but they set themselves professional goals, undergo training in order to become a professional in their field and to achieve success in chosen professional sphere in future. The purpose of the study is to analyze perceptions of student youth about essence of professional success and factors of its achievement. Materials and methods. The study of student youth opinions about professional success is based on results of the author’s research among students of universities of Penza, Saratov (2023–2024), and data analysis of sociological research VTsIOM, FOM. Results. The essential content of “professional success” concept is considered, its components are revealed, ideas of modern students about components and factors of professional success are characterized, and influence of education on future achievement of success in professional field is analyzed. Conclusions. The core of professional success for modern students is high professionalism in work, material wealth, career, as well as authority in their professional sphere. A number of individual qualities are important for its achievement: the ability to set and achieve goals, responsibility, professionalism, competence. Modern students are more focused on the “achievement” model of economic orientations. Although higher education is not the main factor of professional success, it contributes to career growth and material well-being.